ASPEK SOSIAL EKONOMI TANAMAN AREN - Subandi Antaatmadja (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Aren tree is one of the members of palm family. The distribution extends in all Indonesian area. The main produc- tion of aren juice for material of sugar, are aren fruits for food, fiber mode for plait material handcraft, and numeroua utilization. The study of aren trees in Cianjur Concludes :1.The aren trees are found in all districts. 2.The study in a sub district of Cianjur reveals that :a.Cibinong is one of the biggest sub district where aren stands were found.b.Total production of brown sugar in 1986 in this sub district was 549 tons with 831 farmers. Average sugar pro- duction ammounts to 0.661 ton/farmer.c.Average input in aren busines is 2.12 hours/day/house hold.d.The small holder of the aren starch production having capacity of 72 tons/year requires total investment of Rp 1,505,000.- and production cost: Rp 11,140,000.-/year giving the financial earning of Rp 7,500,000.-